Unilateral or single-session bilateral surgery for correction of medial patellar luxation in small dogs: short and long-term outcomes - Clerfond, P.; Huneault, L.; Dupuis, J.; Moreau, M.; Auger, J. (Veterinary and Comparative Orthopaedics and Traumatology, 2014)
Objective: To compare complication rates as well as the short and long-term function of surgical limbs in small dogs with bilateral medial patellar luxation (MPL) undergoing unilateral or single-session bilateral surgery.Methods: Dogs weighing less than 12 kg with bilateral MPL that underwent unilateral (group U) or single-session bilateral surgery (group B) were retrospectively analysed. Data analysed included signalment, grades of luxation, surgical procedures, duration of surgery and anaesthesia, use of antibiotic medications, hospitalization time, complications, function at short-term follow-up, bone healing, and long-term assessment of function by means of a questionnaire.Results: Twenty-four dogs were included in group U and 27 in group B. Groups were similar in signalment and procedures performed. No significant difference was found in overall, minor, and major complication rates between Group U and Group B, nor in the short and long-term function of surgical limbs. Nine out of 21 dogs developed clinical signs on the contralateral stifle in Group U, of which only three underwent corrective surgery.Clinical significance: Single-session bilateral surgery could be offered for dogs with bilateral MPL with complication rates and function of operated limbs similar to unilateral surgery.
Keywords: Patellar luxation; bilateral; complications